(untitled) (Journal of the College of Basic Education, 2022)
This research was the result of a strenuous scientific effort that I made during my stay in Libya to teach there between the years 1997-2000, as I thought that Libyan universities depend on scientific promotion based on scientific research, as is the case in Iraqi universities, so I thought of writing a group of researches in line with the orientation of universities Scientific interest in modern Libyan history, a scientific specialist and focus on the Italian occupation of Libya.